2011
DOI: 10.1007/s00216-011-4895-5
|View full text |Cite
|
Sign up to set email alerts
|

Semi-quantitative analyses of metabolic systems of human colon cancer metastatic xenografts in livers of superimmunodeficient NOG mice

Abstract: Analyses of energy metabolism in human cancer have been difficult because of rapid turnover of the metabolites and difficulties in reducing time for collecting clinical samples under surgical procedures. Utilization of xenograft transplantation of human-derived colon cancer HCT116 cells in spleens of superimmunodeficient NOD/SCID/IL-2Rγnull (NOG) mice led us to establish an experimental model of hepatic micrometastasis of the solid tumor, whereby analyses of the tissue sections collected by snap-frozen procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 28 publications
1
81
0
Order By: Relevance
“…4T1 lung metastasis tissues snap-frozen in liquid nitrogen were dissected to prepare cryosections with 5-µm thickness by use of a cryostat (CM 1900; Leica Microsystems, Wetzlar, Germany). The sections were thaw-mounted on indium-tin oxide slides (Bruker Daltonik GmbH, Bremen, Germany) and were dried in silica gel-containing plastic tubes and, then, sprayed with 9-aminoacridine (9-AA, 20 mg in 4 ml 70% MeOH) by use of a 0.2-mm nozzle calibre airbrush (Procon boy FWA Platinum; Mr Hobby, Tokyo, Japan) to conduct matrix-assisted laser desorption/ionization (MALDI) imaging mass spectrometry in negative ion mode 34,35 . Adjacent sections were fixed with 4% buffered formalin (Nacalai Tesque, Kyoto, Japan) and stained with anti-CD44v antibody 52 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4T1 lung metastasis tissues snap-frozen in liquid nitrogen were dissected to prepare cryosections with 5-µm thickness by use of a cryostat (CM 1900; Leica Microsystems, Wetzlar, Germany). The sections were thaw-mounted on indium-tin oxide slides (Bruker Daltonik GmbH, Bremen, Germany) and were dried in silica gel-containing plastic tubes and, then, sprayed with 9-aminoacridine (9-AA, 20 mg in 4 ml 70% MeOH) by use of a 0.2-mm nozzle calibre airbrush (Procon boy FWA Platinum; Mr Hobby, Tokyo, Japan) to conduct matrix-assisted laser desorption/ionization (MALDI) imaging mass spectrometry in negative ion mode 34,35 . Adjacent sections were fixed with 4% buffered formalin (Nacalai Tesque, Kyoto, Japan) and stained with anti-CD44v antibody 52 .…”
Section: Methodsmentioning
confidence: 99%
“…Together, these results indicated that lung metastasis results in enrichment of ROS-resistant cells with high GSH levels. To examine whether CD44v-expressing cells maintain high GSH levels in vivo, we applied imaging mass spectrometry to visualize GSH and oxidized glutathione (GSSG) in frozen tissue samples 34,35 . CD44v + lung metastases formed by 4T1 cells manifested high levels of GSH but not of GSSG (Fig.…”
Section: Esrp1 Promotes Lung Metastasis Of 4t1 Cellsmentioning
confidence: 99%
“…Cryosections (5 mm) of the liver samples were thaw-mounted on indium-tin oxide slides (8-12 ohm/sq; Sigma; ref. 27). Protocols for the abovementioned experiments were approved by Institutional Committee of Animal Care and Ethics in School of Medicine, Keio University.…”
Section: Maldi-ims Analyses Of Liver Metastases Of Human Colon Cancermentioning
confidence: 99%
“…Fluorescent images of metastatic foci on tissue slices were acquired with a built-in fluorescence microscope and 2 fluorescence mirror units (U-MGFPHO for green fluorescence and U-MWIG3 for red fluorescence; Olympus). Matrix application (27) and acquisition of MALDI imaging data (27) with spatial interval of 20 mm and data processing (27,28) were carried out as described previously. Measurement points with Fucci-green fluorescence were considered to be cells in S þ G 2 -M phases.…”
Section: Maldi-ims Analyses Of Liver Metastases Of Human Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation